Reducing Maternal Depressive Symptoms Through Promotion of Parenting in Pediatric Primary Care. (May 2014) - Berkule, Samantha B.; Cates, Carolyn Brockmeyer; Dreyer, Benard P.; Huberman, Harris S.; Arevalo, Jenny; Burtchen, Nina; Weisleder, Adriana; Mendelsohn, Alan L.
We studied associations between 2 pediatric primary care interventions promoting parental responsiveness and maternal depressive symptoms among low-income mothers. This randomized controlled trial included 2 interventions (Video Interaction Project [VIP], Building Blocks [BB]) and a control group. VIP is a relationship-based intervention, using video-recordings of mother–child dyads to reinforce interactional strengths. BB communicates with parents via parenting newsletters, learning materials, and questionnaires. At mean (SD) child age 6.9 (1.2) months, depressive symptoms were assessed with the Patient Health Questionnaire-9 (PHQ-9), parental responsiveness was assessed with StimQ-I. A total of 407 dyads were assessed. Rates of mild depressive symptoms were lower for VIP (20.6%) and BB (21.1%) than Controls (32.1%, P = .04). Moderate depressive symptoms were lower for VIP (4.0%) compared to Controls (9.7%, P = .031). Mean PHQ-9 scores differed across 3 groups ( F = 3.8, P = .02): VIP mothers scored lower than controls ( P = .02 by Tukey HSD). Parent–child interactions partially mediated VIP-associated reductions in depressive symptoms (indirect effect −.17, 95% confidence interval −.36, −.03).